PENGAWASAN KEARSIPAN OLEH KEPALA TATA USAHA DI MADRASAH ALIYAH NEGERI (MAN) 2 SOLOK SELATAN - Weni Sumarni; Zulfani Sesmiarni; Supratman Zakir; Darul Imi; Ali Mustopa Yakub Simbolon; Ikmal Diandi (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2023)
This research is motivated by the fact that there are still administrative staff members who lack understanding of proper record management, the presence of administrative staff members who do not complete the management of records, and the limitations of facilities and infrastructure, particularly in the field of records management, at Madrasah Aliyah Negeri 2 Solok Selatan. The objectives of this research are to determine the stages of record management at Madrasah Aliyah Negeri 2 Solok Selatan, to understand the supervision process of the head of administration in record management at Madrasah Aliyah Negeri 2 Solok Selatan, and to identify the challenges faced by the administration in supervising record management at Madrasah Aliyah Negeri 2 Solok Selatan. The research method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The subjects of the study are the head of administration and administrative staff. The results of this research indicate that the stages of record management at Madrasah Aliyah Negeri 2 Solok Selatan consist of five stages. The stages are as follows: first, the Creation and Receipt stage; second, the Distribution stage; third, the Utilization stage; fourth, the Maintenance stage; and fifth, the Disposal stage. The supervision process of the head of administration in record management includes the following: first, the Establishment of Standards stage; second, the Determination of Implementation Measurement/Performance Measurement stage; and third, the Action Taking stage. The challenges faced by the head of administration in supervising record management at Madrasah Aliyah Negeri 2 Solok Selatan include the following: first, the presence of administrative staff members who do not complete the management of records; second, the lack of understanding among administrative staff members regarding proper record management; and third, the lack of facilities and infrastructure for records management.